2021
DOI: 10.46770/as.2020.201
|View full text |Cite
|
Sign up to set email alerts
|

Review: Application Of LIBS To Elemental Analysis And Mapping Of Plant Samples

Abstract: Trace minerals and metallic elements play a key role in plant metabolism and function. Therefore, it is important to understand the movement and distribution of trace minerals within various parts of plants in order to understand their metabolic pathways. Information on the localization of minerals can be utilized in the fields of plant science, agriculture, and food technologies. In this context, herein, we review the feasibility of application of laser-induced breakdown spectroscopy (LIBS) as a technique for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Internal elements in plants ( Figure 3 ) can be indicators of the influence of the surrounding environment on plant growth. Every environmental change that occurs can change the composition and abundance of these elements [ 52 ]. Lin and Xing concluded that ZnO nanoparticles at an initial concentration of 2000 mg/L were toxic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internal elements in plants ( Figure 3 ) can be indicators of the influence of the surrounding environment on plant growth. Every environmental change that occurs can change the composition and abundance of these elements [ 52 ]. Lin and Xing concluded that ZnO nanoparticles at an initial concentration of 2000 mg/L were toxic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can provide the chemical composition and information on molecular structure of the samples and the analysis can also be completed in only a few seconds. 61 Another advantage of this method is the possibility of real time characterization of the samples which is convenient to re-collect the sample if there is a problem. Previous studies have shown that LIBS can be used to distinguish plastics from natural materials and identify the types of basic polymers, especially in distinguishing C-O and C-C skeleton, PE, and PP particles.…”
Section: Application Of Atomic Spectrometry In Mnpls Analysismentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy (LIBS) is a rapidly developing chemical element analysis technology that has been widely used in the detection of alloys, 5–7 plant materials, 8–10 food and nutrition, 11–13 rocks, 14–16 and soils. 17–19 As a fast, online, pollution-free, and low-cost technology, it is well suited for the approximate analysis of milk powder.…”
Section: Introductionmentioning
confidence: 99%